Rancang Bangun Alat Pengendali Hama Wereng Mekanik Menggunakan LED dan Alat Penyedot - Satria Pinandita (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Rice farmers in agricultural business experiences many obstacles in field, particularly pest attack. The farmers currently use pesticides to control brown planthoppers. Pesticides are chemicals which are very harmful and toxic to human, natural predator, and environment. Planthoppers are attracted to light; thus, a mechanical device which was supported with lamp and shuck had been constructed to attract planthoppers. The method used was a designed device using solid work. The hardware and software was designed in brown planthoppers controller in order to monitor the input of censor which was used to be analyzed and transmitted to the sucking motor driver. The device was tested in the laboratory and the field. Results of laboratory test showed that brown plant hoppers controller worked properly. The device responded input from three censors and was able to suck up the Styrofoam cuts. Results of field test indicated that the device using white LEDs captured 149 animals; blue LED captured 148 animals; red LED captured 115 animals; green LED captured 72 animals; and yellow LED captured 66 animals.